Diversification and ecosystem services for conservation agriculture: Outcomes from pastures and integrated crop–livestock systems. Issue 2 (11th March 2013) - Sanderson, Matt A.; Archer, David; Hendrickson, John; Kronberg, Scott; Liebig, Mark; Nichols, Kris; Schmer, Marty; Tanaka, Don; Aguilar, Jonathan
Abstract: Conservation agricultural systems rely on three principles to enhance ecosystem services: (1) minimizing soil disturbance, (2) maximizing soil surface cover and (3) stimulating biological activity. In this paper, we explore the concept of diversity and its role in maximizing ecosystem services from managed grasslands and integrated agricultural systems (i.e., integrated crop–livestock–forage systems) at the field and farm level. We also examine trade-offs that may be involved in realizing greater ecosystem services. Previous research on livestock production systems, particularly in pastureland, has shown improvements in herbage productivity and reduced weed invasion with increased forage diversity but little response in terms of animal production. Managing forage diversity in pastureland requires new tools to guide the selection and placement of plant mixtures across a farm according to site suitability and the goals of the producer. Integrated agricultural systems embrace the concept of dynamic cropping systems, which incorporates a long-term strategy of annual crop sequencing that optimizes crop and soil use options to attain production, economic and resource conservation goals by using sound ecological management principles. Integrating dynamic cropping systems with livestock production increases the complexity of management, but also creates synergies among system components that may improve resilience and sustainability while fulfilling multiple ecosystem functions. Diversified conservation agricultural systems can sustain crop and livestock production and provide additional ecosystem services such as soil C storage, efficient nutrient cycling and conservation of biodiversity.